Electrophysiological event-related-potentials & their association with genome-wide-associated risk variants in schizophrenia - O'Donoghue, Thérèse (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Psychiatry, 2012)
This thesis describes the use of electrophysiological event- related-potentials as a method for understanding, at the cortical level, the functional significance of putative schizophrenia susceptibility genes identified in recent genome-wide- association-studies.
Keywords: Psychiatry, Ph.D.; Ph.D. Trinity College Dublin